Effect of Heat Treatment on Properties of LGJW20 Steel - Li, Ping; Liu, Ning; Zhu, Shaofeng; Chen, Xinjie (Asian Journal of Chemistry, 2014)
This paper prepared steel composites LGJW20 containing 20 % tungsten carbide particles by centrifugal casting method and its substrate material was GCr15 bearing steel. In this study, the material was treated by heat treatment. The metallographic analysis, XRD and SEM, and the performance of the alloy was represented with Vickers hardness and bending strength. Organizational defects were effectively eliminated in annealing process. When the material was quenched at 980 ºC, martensitic structure is maximized and Vickers hardness reaches the maximum, during which the quenching effect is the best.